جمالية أسلوب التهكم في مقالات الإبراهيمي -دراسة في نماذج مختارة - بوراس نور الهدى (My University, 2023)
Summary: This study dealt with an important style of discourse, a style of sarcasm, its purpose is to highlight the aesthetic meanings of sarcasm generated by the methods of construction and graphic images that came in the articles of Bashir Ibrahimi, and has looked at it from two sides: the theoretical side and the practical side، in the theoretical side provides the concept of sarcasm language، and idiomatically، then the emergence of the style of sarcasm and its development، and its relationship to neighboring terms. Then the definition of Ibrahimi, the practical side studied structural methods and graphic images by definition، and extracting the satirical meanings generated by them، by presenting examples from the articles of Bashir Ibrahimi. This study concluded that this method has wide connotations، and acquires great importance in communication, because it has a great impact on the soul. ------------------------ ملخص: تناولت هذه الدراسة أسلوبا مهما من أساليب الخطاب، وهو أسلوب التهكم، غايتها أن تبرز جمالية المعاني التهكمية المتولدة عن الأساليب الإنشائية و الصور البيانية التي جاءت في مقالات البشير الإبراهيمي، و قد نظرت إليه من جانبين: جانب نظري و جانب تطبيقي، ففي الجانب النظري يقدم مفهوم التهكم لغة، و اصطلاحا، ثم ظهور أسلوب التهكم وتطوره، وعلاقته بالمصطلحات المجاورة، ثم التعريف بالإبراهيمي، أما الجانب التطبيقي فدرس الأساليب الإنشائية و الصور البيانية بتعريفها، و استخراج المعاني التهكمية التي تولدت عنها، و ذلك بعرض أمثلة من مقالات البشير الإبراهيمي. وخلصت هذه الدراسة إلى أن هذا الأسلوب ذو دلالات واسعة، و يكتسب أهمية كبيرة في التواصل، لأن له أثر كبير في النفوس ------------------ résumé: Cette étude a traité d'une méthode importante de discoure, qui est le style de sarcasme. L'esthétique des significations satiriques générées par les méthodes structurelles et les images graphiques qui sont entrées dans les articles d'al Bachir Al –Ibrahimi, et je l'ai examiné de deux cotés, un coté théorique et un coté appliqué, dans le coté théorique présent le concept de langage et de terminologie satirique, puis l'émergence du style de la satire, son développement et sa relation aux termes voisins, puis la définition quant au coté appliqué, il a étudié les méthodes structurelles et les images graphique en les définissant et en extrayant les significations ironiques qui les générées Et par la présentation des articles d'Al-Bachir Al-Ibrahimi. Cette étude conclut que cette méthode a une portée considérable et revet une grande importance dans la communication, parce qu'elle a un impact important sur les ames…